Nações, fronteiras e relações étnicas na comunidade indígena-quilombola do Baixão (Vitória da Conquista, BA) - Vivian Ingridy de Carvalho Lima; Washington Santos Nascimento (Ciências Sociais Unisinos)
In this article we intend to discuss the history of the Baixão community, located in the rural area of Vitória da Conquista (Bahia, Brazil), formed from the processes of mixing and miscegenation between indigenous and African. Through the analysis of the memories of its residents, we intend to show the process of construction of a new identity, the quilombola identity due to a recent territorial certification process.